(3OQGSI JMdjdjI JCUjdjI JWHjbjIs - (3CMeO(B, (3YHO GddWjas ((3GdbGgQI(B:s (3OGQ GdfgVI GdYQHjI(B,s)
(3eGgjI GdCehGd GdYGeI(B- (3Gdeaghe GdLfGFj ddeGd hGdehXa GdYGe(B- (3fWGb GdMeGjI GdLfGFjI ddeGd GdYGe(B- (3HYV GdCMcGe GdNGUI aj LQGFe GdeGd GdYGe(B.s
Keywords: (3GdLQGFe(B- (3GdCehGd GdYGeIs; (3GdeGdjI GdYGeI(B- (3bhGfjf hCfXeIs; (3LQGFe GdCehGds